Examining the effectiveness of bored pile coral for coral rehabilitation - NOVITA PERMATA PUTRI; MUHAMMAD RIFAT MUHARAM; ABDULRAHMAN RITONGA; CORINA DEWI RUSWANTI; DIAN ARTHEN; MUNASIK MUNASIK (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Putri NP, Muharam MR, Ritonga A, Ruswanti CD, Arthen D, Munasik. 2024. Examining the effectiveness of bored pile coral for coral rehabilitation. Biodiversitas 25: 153-161. Semut Island is located in Kiabu Village, Anambas Islands, Riau, Indonesia, and has suffered significant damage to its coral cover due to blast fishing. To address this issue, Anambas Foundation initiated a coral reef rehabilitation on Semut Island using a customized artificial reef called Bored Pile Coral (BPC), a cylindrical structure made of concrete hammered into the seabed. This research aims to examine the effectiveness of BPC by monitoring its performance. Therefore, from February 2022 to January 2023, 1,500 BPCs were deployed and attached with corals covering an area of 170 m2. We quantified five ecological indicators, i.e., coral cover, survival rate, recruitment, growth rates, and fish biomass. Results showed an increase in coral cover from 3.8% to 8%. The survival rate was 64%, and the mean monthly growth rates varied among three genera: Pocillopora sp. (0.235±0.02 month-1), Acropora sp. (0.22±0.03 month-1) and Porites sp. (0.08±0.02 month-1). The monthly mean fish biomass data showed the biomass was 427,25 Kg/Ha and increased 3,9 times since the beginning of the research. BPC's structure has been proven to act as stable media for hard corals, although the modification may be necessary to enhance structural complexity and suitability for carnivorous fish habitats.